2013
DOI: 10.1016/j.expneurol.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of parkin in the rat nigrostriatal dopamine system protects against methamphetamine neurotoxicity

Abstract: Methamphetamine (METH) is a central nervous system psychostimulant with a high potential for abuse. At high doses, METH causes a selective degeneration of dopaminergic terminals in the striatum, sparing other striatal terminals and cell bodies. We previously detected a deficit in parkin after binge METH in rat striatal synaptosomes. Parkin is an ubiquitin-protein E3 ligase capable of protecting dopamine neurons from diverse cellular insults. Whether the deficit in parkin mediates the toxicity of METH and wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 66 publications
2
29
0
Order By: Relevance
“…We have previously shown that binge METH decreases the levels of parkin by approximately 42‐48% in striatal synaptosomes (Moszczynska and Yamamoto ) and that parkin overexpression in the nigrostriatal system protects against METH neurotoxicity in adult rats (Liu et al . ). In this study, METH alone, but not BA alone, significantly decreased parkin immunoreactivity in striatal synaptosomal preparations at 1 h after METH; however, the 28%‐deficit in parkin was not sufficient to trigger degeneration of monoaminergic terminals in adolescent rat striatum.…”
Section: Discussionmentioning
confidence: 97%
“…We have previously shown that binge METH decreases the levels of parkin by approximately 42‐48% in striatal synaptosomes (Moszczynska and Yamamoto ) and that parkin overexpression in the nigrostriatal system protects against METH neurotoxicity in adult rats (Liu et al . ). In this study, METH alone, but not BA alone, significantly decreased parkin immunoreactivity in striatal synaptosomal preparations at 1 h after METH; however, the 28%‐deficit in parkin was not sufficient to trigger degeneration of monoaminergic terminals in adolescent rat striatum.…”
Section: Discussionmentioning
confidence: 97%
“…Literature data also show that the cell-permeable Parkin can compensate for intrinsic limitations in the Parkin response and provide a therapeutic strategy to augment Parkin activity in vivo (Duong et al, 2014). Toxicologically, induction of Parkin expression can protect striatal dopaminergic terminals against methamphetamine (METH)-induced neurotox-icity (Liu et al, 2013a). Logically, a reduction in Parkin expression, as observed in this study, could weaken the protective effect of Parkin in the pathoetiology of Parkinson’s disease or related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…[125]. Conversely, over-expression of Parkin protects rat dopaminergic neurons from the toxic effects of acute methamphetamine, in vivo [126]. Future studies are necessary in order to examine whether genetic variability in Parkin and other UPS proteins renders the individual more susceptible to dopaminergic cell damage resulting from methamphetamine use.…”
Section: Environmental Modulators In Pdmentioning
confidence: 99%